Possibilities for automated programming style assessment in informatics olympiads - Skūpienė, Jūratė (Lietuvos matematikos rinkinys, 2021)
Programming Style is an important part of program quality and it should be taken into account while assessing programs designedby competitors in informatics. In InternationalOlympiad in Informatics grading is automated and based on testing results only, while programming style is not taken into account. However there exists practice in universities in programming courses where programming style of submitted programs is evaluated automatically. The paper reviews existing experience and discusses possibilities for automated grading of programming style in informatics olympiads.
Keywords: teachning programming; algorithms; programming style; automated grading